Incidence and feasibility of coronary access after transcatheter aortic valve replacement. Issue 5 (8th January 2020) - Nai Fovino, Luca; Scotti, Andrea; Massussi, Mauro; Fabris, Tommaso; Cardaioli, Francesco; Rodinò, Giulio; Matsuda, Yuji; Frigo, Francesca; Fraccaro, Chiara; Tarantini, Giuseppe
Abstract: Background: Incidence of coronary access (CA) after transcatheter aortic valve replacement (TAVR) at long‐term follow‐up remains unknown. CA and percutaneous coronary intervention (PCI) after TAVR might present technical challenges, particularly with supra‐annular devices. Methods: Patients undergoing CA after being treated with TAVR at our institution were included in the study. Coronary interventions for coronary obstruction during TAVR procedure were excluded. Incidence, feasibility and outcomes of CA after TAVR were analyzed. Results: Out of 912 patients aged 80 ± 7 years treated with TAVR at our institution between 2007 and 2018, 48 (5.3%) underwent CA at a median follow up of 769 [363–1, 471] days. Twenty‐one had received a SAPIEN XT, 15 a SAPIEN 3, 6 Corevalve, 2 Evolut Pro, 2 JenaValve, and 2 Lotus valve. PCI was indicated in 26 (54%) cases. Seventeen (35%) procedures were performed for acute coronary syndromes (ACS). Independent predictors of CA after TAVR were younger age, previous PCI, and CABG. CA of both vessels was feasible in all patients with an intra‐annular device, while the right coronary artery was not engaged in two patients with a supra‐annular valve. PCI was successful in all but one case. All‐cause mortality was similar between patients needing CA for ACS and those who had other clinical indications. Conclusions: In this high‐risk AS population, incidence of CA after TAVR at long‐term follow‐up was rather low. CA and PCI were safe and successful in most cases, with a lower rate of selective CA for supra‐annular devices.